Density functional theory study on the interaction between metalloporphyrins and NH3. Issue 8 (5th June 2012) - Cao, Zhenfeng; Chen, Qibin; Lu, Yunxiang; Liu, Honglai; Hu, Ying
Abstract The binding behaviors of eight bivalent metalloporphyrins (MPs) (MZn, Mg, Cu, Mn, Fe, Co, Ni, and Cd) with NH3 were investigated by density functional theory. For both MPs and corresponding complexes MPs‐NH3, good linear correlations are found between the partial charge on metal M and that on atom N (nitrogen of porphyrin) as well as the MN bond length. Natural population and frontier orbital analysis demonstrate that charge transfer in CoP‐NH3 is much easier and greater. As a consequence of the charge transfer and the hybridization of molecular energy levels, striking disparities of electronic properties of MPs‐NH3 are observed. Particularly, a modest linear relationship is obtained between the magnitude of charge transfer and the binding energy. The much greater Fukui functions of CoP, together with its larger binding strength, suggest that CoP is more favorable to the interaction with NH3, which might be a promising sensing material to response NH3. © 2013 Wiley Periodicals, Inc.